Academic Procrastination among Students of the Faculty of Education at Hail University - Wedad M. Alkferi (Sultan Qaboos University, 2016)
This study aimed to investigate the prevalence of academic procrastination among students in the Faculty of Education at the University of Hail, and applied on a sample of 360 female students in the second semester of the academic year 2014 / 2015 selected randomly. To achieve the objectives of the study a measure of academic procrastination was developed. The researcher used mean & standard deviation, to conclude the findings. The findings of the study showed that an average level of procrastination among female students. Differences were found statistically significant due to the place of residence for the city of Hail, while there were no significant due to the variable marital status differences. The researcher recommended worthwhile educational institutions develop plans and programs needed to reduce the phenomenon of academic procrastination and raise the motivation of university students.